DETERMINATION OF THE PARAMETERS OF SUBSURFACE DRIP IRRIGATION SYSTEMS ON THE BASE OF MOISTURE TRANSPORT MODELING - Romashchenko, М.; Bohaienko, V.; Sardak, А.; Nykytiuk, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper considers the problem of determining the depth of drip pipelines installation and the distance between the pipelines within the design of subsurface drip irrigation systems along with the assessment of pulse irrigation regime efficiency. The corresponding optimization problem has an objective function that assesses costs of creating and operating the system and is solved by a genetic algorithm. For each set of system parameters' values the scheduling of irrigation during the growing season is modeled according to the specified pre-irrigation threshold. The simulation is based on the two-dimensional Richards equation approximated by a finite-difference scheme. The characteristics of crop development are determined according to the model based on the change of development stages with the accumulation of a given amount of active temperatures. To take into account the variability of weather conditions modeling is performed for a series of randomly generated weather scenarios.
Keywords: subsurface drip irrigation; pulse irrigation; moisture transport; modeling; optimization